Correlation of automated cell counter RBC histograms and peripheral smear in anemia typing - Meena, Hariom; Pruthviraj CS,; Gupta, Rakesh; Guru, Aayushi; Suresh Kumar Sutrakar, (Asian Journal of Medical Sciences, 2023)
Background: Red blood cell (RBC) indices and histogram obtained from automated hematology gives an idea about the morphological changes in anemia and therefore forms the fundamental process for diagnosis of anemia. Along with the peripheral smear, they can be used for anemia typing and to interpret the cause of anemia. Aims and Objectives: (1) Interpretation of histograms in normal persons and patients with different types of anemia. (2) Anemia typing based on RBC histograms complemented with Peripheral smear examination. Materials and Methods: The present prospective study is conducted in Haematology section of Department of Pathology, Shyam Shah Medical College and Sanjay Gandhi Medical Hospital Rewa, Madhya Pradesh. A total of 1000 patients blood sample is collected for complete blood count and anemia typing irrespective of age and gender and examined over a period of 1 year from August 2021 to July 2022. The patient’s blood sample is collected in EDTA vacutainer and analyzed on the basis of histogram obtained and peripheral smear slide prepared. Results: In the present study, we noted that the predominant age group affected was 20–30 years. Peripheral smear finding shows normocytic normochromic anemia was seen in 6% cases (60/1000), microcytic hypochromic anemia seen in 24.2% cases (242/1000), macrocytic anemia seen in 14% cases (140/1000), dimorphic anemia seen in 50.2% cases (502/1000), and hemolytic anemia seen in 5.6% cases (56/1000). This peripheral smear finding shows well correlation with findings of histogram pattern and RBC indices, where normocytic normochromic seen in 6.4% of cases (64/1000), microcytic hypochromic anemia seen in 24.4% of cases (244/1000), macrocytic anemia seen in 13.8% of cases (138/1000), dimorphic anemia seen in 49.5% of cases (495/1000), and hemolytic anemia seen in 5.9% of cases (59/1000). The most common anemia is dimorphic anemia (combined nutritional deficiency) in 49.5% cases followed by microcytic hypochromic anemia in 24.4% of cases based on histogram findings along with RBC indices. Conclusion: Histogram guides a technologist about the cases that need actual detailed peripheral smear examination by experts. Our study shows a well correlation in findings of automated hematology analyzer with the microscopic examination. Histogram alone could be used as screening method and when combined with peripheral blood smear findings, they act as useful supplement and by correlating findings of both methods, we could diagnose majority of anemia.